A Smoking Club. - (:unkn) unknown (Aitken, J., 1793)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Great Britain -- Politics and government -- 1760-1820 -- Caricatures and cartoons